2020
DOI: 10.3390/brainsci10120993
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Role of Dynamic Multisensory Processing Using Molecular Genetic Data in Dyslexia

Abstract: Although substantial heritability has been reported and candidate genes have been identified, we are far from understanding the etiopathogenetic pathways underlying developmental dyslexia (DD). Reading-related endophenotypes (EPs) have been established. Until now it was unknown whether they mediated the pathway from gene to reading (dis)ability. Thus, in a sample of 223 siblings from nuclear families with DD and 79 unrelated typical readers, we tested four EPs (i.e., rapid auditory processing, rapid automatize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 143 publications
0
9
2
Order By: Relevance
“…This independent cumulative effect affects the nal behavioral outcome through digit RAN, which means that, coincident with models of multiple de cits, the direct in uence of genetic variation is limited [1,69]. Contrary to our ndings, previous studies did not provide su cient evidence for RAN as an EP [31,70], whereas in our study, RAN was found to mediate gene-phenotype associations. This might be due to different measurement methods of endophenotypes, different languages and fewer selected SNPs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This independent cumulative effect affects the nal behavioral outcome through digit RAN, which means that, coincident with models of multiple de cits, the direct in uence of genetic variation is limited [1,69]. Contrary to our ndings, previous studies did not provide su cient evidence for RAN as an EP [31,70], whereas in our study, RAN was found to mediate gene-phenotype associations. This might be due to different measurement methods of endophenotypes, different languages and fewer selected SNPs.…”
Section: Discussioncontrasting
confidence: 99%
“…Genome-wide association studies reported the effects of SNPs on RAN, and classical twin studies found heritability estimates ranging from 0.56 to 0.70 for RAN [26][27][28][29][30]. The latest results explored RNA as an endophenotype that mediates the association between genes and reading ability [14,31]. Therefore, RNA, according to the criteria for EPs [16,32], was investigated as a mediator in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently so far, studying the genetic basis of reading difficulties has not added much to our understanding of the neural basis of reading. Nevertheless one of these genes, ROBO1, which helps to guide axons to their correct destinations during brain development, has been found to be associated specifically with visual motion sensitivity (a putative visual temporal processing marker) in dyslexics ( Mascheretti et al, 2020 ). This is perhaps a first step in unraveling how gene variants might endow impaired visual processing to people with dyslexia.…”
Section: Genetic Backgroundmentioning
confidence: 99%
“…Other genes have been linked to dyslexia. For instance, ROBO1 affects auditory and visual motion processing that predict for reading achievement ( Mascheretti et al, 2020 ) and vocal learning in animals ( Wang et al, 2015 ); the gene has been associated with increased interneuron migration into the cerebral cortex, as well as altered inter and intrahemispheric connectivity ( Andrews et al, 2006 ). Homozygous deletions of Robo1 in the mouse are also associated with occasional heterotopias [ Anthoni et al, 2012 ; also see review by Gonda et al (2020) ].…”
Section: Animal Models Of Dyslexiamentioning
confidence: 99%